2007
DOI: 10.1021/ic701494p
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Fluoride Ion Sensing by Polyborylated Ferrocenes:  Structural Influences on Thermodynamics and Kinetics

Abstract: The thermodynamic factors underlying the use of ferroceneboronic esters as electrochemical or colorimetric fluoride ion sensors have been investigated through the synthesis of a range of systematically related derivatives differing in the number/nature of the boronic ester substituents and in the nature of ancillary ligands. Thus, if the shift in electrochemical potential associated with the conversion of one (or more) boronic ester group(s) to anionic boronate(s) on fluoride binding is sufficient to allow oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…A preliminary investigation by cyclic voltammetry revealed that FcB shows quantitative shifts of −567 and −702 mV for the Fc + /Fc redox couple in the presence of excesses of CN − and F − , respectively, in CH 2 Cl 2 / n Bu 4 NPF 6 (Figure c and Table ), indicating a significant increase in the binding constants upon one‐electron oxidation . This is consistent with the increases in the density functional theory (DFT)‐calculated HOMO levels of FcB–CN − and FcB–F − compared with that of FcB (Figure a), as well as previous reports on the electrochemical responses of FcB and Fc boronic acid derivatives . Thus, conversion of the three‐coordinated boron to the four‐coordinated borate can change the relative electron‐donating abilities of the redox sites, with different guest anions serving to modulate Δ G 0 .…”
Section: Resultssupporting
confidence: 90%
“…A preliminary investigation by cyclic voltammetry revealed that FcB shows quantitative shifts of −567 and −702 mV for the Fc + /Fc redox couple in the presence of excesses of CN − and F − , respectively, in CH 2 Cl 2 / n Bu 4 NPF 6 (Figure c and Table ), indicating a significant increase in the binding constants upon one‐electron oxidation . This is consistent with the increases in the density functional theory (DFT)‐calculated HOMO levels of FcB–CN − and FcB–F − compared with that of FcB (Figure a), as well as previous reports on the electrochemical responses of FcB and Fc boronic acid derivatives . Thus, conversion of the three‐coordinated boron to the four‐coordinated borate can change the relative electron‐donating abilities of the redox sites, with different guest anions serving to modulate Δ G 0 .…”
Section: Resultssupporting
confidence: 90%
“…Triarylboron compounds have recently emerged as an attractive and versatile class of optoelectronic materials. By harnessing the electron‐accepting nature of the boron center, researchers have successfully developed highly selective and sensitive chemical sensors,1–3 bright photo‐ and electroluminescent materials,4 and compounds with impressive nonlinear optical properties5 based on triarylboranes. Furthermore, these compounds can act as efficient electron‐transport materials due to stabilization of radical anions by the Lewis acidic boron atom, making them particularly attractive for use as bifunctional active layers for organic light‐emitting diodes (OLEDs) 4…”
Section: Introductionmentioning
confidence: 99%
“…This assignment is consistent with ferrocenium itself 26 and the boronate ester of B reported elsewhere. 27 The second band is broad, in the near-infrared (NIR) region, and is assigned to the IVCT transition between the Fc groups. Gaussian deconvolution of the IVCT transition band of Cester + gave the spectroscopic parameters of energy, intensity, and bandwidth at half-height (υ max = 4460 cm −1 , ε max = 752 M −1 cm −1 , Δυ 1/2 = 4260 cm −1 ).…”
Section: Synthesis and Characterization Of Neutral Complexesmentioning
confidence: 99%